I came across the use of Descartes' theorem while solving a question.I searched it but I could only find the theorem but not any proof.Even Wikipedia also, just states the theorem!!I want to know the procedure to find the radius of the Soddy Circle??

I apologize if its duplicate and to mention it is not a homework.

  • $\begingroup$ If you search "Proof of Descartes Theorem" on google yields this proof as the first answer on my search. It seems pretty understandable, but longer than I would want to reproduce here. $\endgroup$ – davidlowryduda Jul 29 '14 at 17:52
  • $\begingroup$ i read that but its not clear to me..till i understood it calculates the radius of incircle formed but i want to calculate the radius of inner or outer Soddy Circle $\endgroup$ – rock321987 Jul 29 '14 at 17:54

Part I - Proof of Soddy-Gosset theorem (generalization of Descartes theorem).

For any integer $d \ge 2$, consider the problem of placing $n = d + 2$ hyper-spheres touching each other in $\mathbb{R}^d$. Let $\vec{x}_i \in \mathbb{R}^d$ and $R_i \in \mathbb{R}$ be the center and radius for the $i^{th}$ sphere. The condition for these spheres touching each other can be expressed as:

$$|\vec{x}_i - \vec{x}_j| = | R_i + R_j | \quad\text{ for }\quad 1 \le i < j \le n$$

or equivalently

$$|\vec{x}_i - \vec{x}_j|^2 = (R_i + R_j)^2 - 4R_iR_j\delta_{ij}\quad\text{ for }\quad 1 \le i, j \le n\tag{*1}$$

where $\;\delta_{ij} = \begin{cases}1,&i = j\\0,& i \ne j\end{cases}\;$ is the Kronecker delta.

Since the $n = d+2$ points $\vec{x}_i$ live in $\mathbb{R}^d$, the $d+1$ vectors $\vec{x}_2 - \vec{x}_1, \vec{x}_3 - \vec{x}_1, \ldots, \vec{x}_n - \vec{x}_1$ are linear depedent, this means we can find $n-1$ numbers $\beta_2, \beta_3, \ldots, \beta_n$ not all zero such that $$\sum_{k=2}^n \beta_k (\vec{x}_k - \vec{x}_1 ) = \vec{0}$$ Let $\beta_1 = -(\beta_2 + \ldots + \beta_n)$, we can rewrite this relation in a more symmetric form:

$$ \sum_{k=1}^n \beta_k = 0 \quad\text{ and }\quad \sum_{k=1}^n \beta_k \vec{x}_k = \vec{0} \quad\text{ subject to some }\;\; \beta_k \ne 0 $$

If we fix $j$ in $(*1)$, multiple the $i^{th}$ term by $\beta_i$ and then sum over $i$, we get

$$ \sum_{i=1}^n\beta_i |\vec{x}_i|^2 = \sum_{i=1}^n\beta_i R_i^2 + 2 \left( \sum_{i=1}^n \beta_i R_i \right) R_j - 4R_j^2 \beta_j $$ This leads to $$4R_j^2 \beta_j = 2 A R_j + B \quad\text{ where }\quad\ \begin{cases} A &= \sum\limits_{i=1}^n \beta_i R_i\\ B &= \sum\limits_{i=1}^n\beta_i ( R_i^2 - |\vec{x}_i|^2 ) \end{cases} \tag{*2} $$ Divide $(*2)$ by $R_j$ and sum over $j$, we get

$$4A = 2nA + B\sum_{j=1}^n\frac{1}{R_j}\quad\iff\quad A = -\frac{B}{2d}\sum_{j=1}^n\frac{1}{R_j}\tag{*3}$$

A consequence of this is $B$ cannot vanish. Otherwise $B = 0 \implies A = 0$ and $(*2)$ implies all $\beta_j = 0$ which is clearly isn't the case.

Divide $(*2)$ by $R_j^2$ and sum over $j$, we get

$$0 = 4\sum_{j=1}^n \beta_j = 2A\sum_{j=1}^n\frac{1}{R_j} + B\sum_{j=1}^n\frac{1}{R_j^2}$$

Combine with $(*3)$, the RHS becomes

$$B \left( \sum_{j=1}^n \frac{1}{R_j^2} - \frac{1}{d}\left( \sum_{j=1}^n\frac{1}{R_j}\right)^2\right) = 0 \quad\iff\quad \left( \sum_{j=1}^n\frac{1}{R_j}\right)^2 = d\sum_{j=1}^n \frac{1}{R_j^2}\tag{*4} $$ The RHS of $(*4)$ is sometimes called Soddy-Gosset theorem. When $d = 2$, it reduces to the Descartes four circle theorem, the theorem we wish to prove: $$\left( \frac{1}{R_1} + \frac{1}{R_2} + \frac{1}{R_3} + \frac{1}{R_4} \right)^2 = 2 \left( \frac{1}{R_1^2} + \frac{1}{R_2^2} + \frac{1}{R_3^2} + \frac{1}{R_4^2} \right) $$

Part II - Construction of inner/outer Soddy hyper-spheres

There is an interesting side-product of the proof in Part I. $\beta_k$ is determined up to an overall scaling factor. If we normalize $\beta_k$ such that $B = 4$, $(*2)$ and $(*3)$ together allows us to derive an explicit expression for $\beta_j$

$$\beta_j = \frac{1}{R_j^2} - \left(\frac{1}{d} \sum_{k=1}^n \frac{1}{R_k}\right)\frac{1}{R_j}\tag{*5}$$

We can use this relation to construct the inner and outer Soddy hyper-spheres.

Assume we already have $n-1 = d+1$ hyper-spheres touching among themselves. The inner Soddy hyper-sphere is the sphere outside all these $n-1$ spheres and yet touching all of them.
Let $\vec{x}_k$ and $r_k$ be the center and radius for the $k^{th}$ hyper-sphere for $1 \le k < n$. Let $\vec{x}_{in}$ and $r_{in}$ be the center and radius of the inner Soddy hyper-sphere. If we let $$\vec{x}_n = \vec{x}_{in}\quad\text{ and }\quad R_k = \begin{cases}r_k,& 1 \le k < n\\ r_{in},& k = n\end{cases}$$ discussions in Part I tell us

$$\left( \frac{1}{r_{in}} + \sum_{k=1}^{n-1} \frac{1}{r_k} \right)^2 = d \left( \frac{1}{r_{in}^2} + \sum_{k=1}^{n-1} \frac{1}{r_k^2} \right)\tag{*6a}$$

We can use this to determine $r_{in}$. If the $n-1$ points $\vec{x}_1, \vec{x}_2, \ldots, \vec{x}_{n-1}$ are in general position, i.e. they are vertices of a non-degenerate $d$-simplex, the $d$ vectors $\vec{x}_2 - \vec{x}_1, \ldots, \vec{x}_{n-1} - \vec{x}_1$ will be linearly independent. This implies there exists $d$ coefficients $\gamma_2, \gamma_3, \ldots, \gamma_{n-1}$ such that

$$\vec{x}_{in} - \vec{x}_1 = \gamma_2 (\vec{x}_2 - \vec{x}_1) + \ldots + \gamma_{n-1} ( \vec{x}_{n-1} - \vec{x}_1 )$$

A consequence of this is $\beta_n \ne 0$. This means we can use $(*5)$ and the relation $\sum\limits_{k=1}^n \beta_k \vec{x}_k = \vec{0}$ to compute the center $\vec{x}_{in}$ of the inner Soddy hyper-sphere.

For the outer Soddy hyper-sphere. It is a sphere that contains the original $n-1$ spheres and touching each of them. Let $\vec{x}_{out}$ and $r_{out}$ be the center and radius of the outer Soddy hyper-sphere. The touching condition now takes the form:

$$\begin{array}{ccccl} |\vec{x}_{out} - \vec{x}_j | &=& | r_{out} - r_j |\quad & \text{ for }\quad & 1 \le j < n\\ |\vec{x}_i - \vec{x}_j | &=& | r_i + r_j | \quad & \text{ for }\quad & 1 \le i < j < n \end{array} $$ Once again, if we let $$\vec{x}_n = \vec{x}_{out}\quad\text{ and }\quad R_k = \begin{cases}r_k,& 1 \le k < n\\ -r_{out},& k = n\end{cases}$$ we can repeat discussions in Part I to obtain $$\left( -\frac{1}{r_{out}} + \sum_{k=1}^{n-1} \frac{1}{r_k} \right)^2 = d \left( \frac{1}{r_{out}^2} + \sum_{k=1}^{n-1} \frac{1}{r_k^2} \right)\tag{*6b}$$ We can use this to determine $r_{out}$. Once again, if $\vec{x}_1,\ldots,\vec{x}_{n-1}$ are in general position, we will find $\beta_n \ne 0$. As a result, we can use $(*5)$ to compute $\vec{x}_{out}$, the center of the outer Soddy hyper-spheres, from the remaining centers.

If one compare $(*6a)$ and $(*6b)$, they are very similar, $r_{in}$ and $-r_{out}$ are the two roots of the same equation in $R$.

$$\left( \frac{1}{R} + \sum_{k=1}^{n-1} \frac{1}{r_k} \right)^2 = d \left( \frac{1}{R^2} + \sum_{k=1}^{n-1} \frac{1}{r_k^2} \right)$$

If the two roots of this equation has different sign, the positive root will be the inner Soddy radius $r_{in}$, the negative root will be $-r_{out}$, the negative of the outer Soddy radius.

  • $\begingroup$ This is probably spam, but I had to say it. The proof of achille hui is complete in every sense of the word. But still not accepted. What more does the OP want? Sadly I can only contribute +1. I don't think this can be bettered. $\endgroup$ – shadow10 Aug 1 '14 at 14:37
  • 1
    $\begingroup$ Very nice proof - probably not written off the top of your head. $\endgroup$ – marty cohen Oct 22 '14 at 1:22
  • $\begingroup$ @martycohen I have this proof in my head for more than a year. Part of the proof dated back to the dates when I discuss math on sci.math instead of math.SE. $\endgroup$ – achille hui Oct 22 '14 at 1:37
  • $\begingroup$ Good old sci.math. I used to spend a lot of time there. Wonder if Archimedes Plutonium is still there with his disproof of Fermat's last theorem and other stuff. $\endgroup$ – marty cohen Oct 22 '14 at 1:40
  • 1
    $\begingroup$ @DevanshSehta $A = B = 0 \implies 4R_j^2 \beta_j = 2 A R_j + B = 0 \implies \beta_j = 0$ because $R_j \ne 0$. $\endgroup$ – achille hui Jun 28 '18 at 20:20

In high-school, my geometry teacher mentioned the Soddy-Gosset theorem and I had been curious about its proof ever since. About 5 years ago, I decided to attempt to prove it and came up with a nice proof and a corollary that, according to my investigation, was unknown, at least in the form that I have.

The first section below is taken from a paper I wrote at that time. The later sections are a clarification of the later parts of that paper.

Tangent Spheres

Suppose that the sphere with radius $r_1$ and center $c_1$, $(c_1,r_1)$, and the sphere with radius $r_2$ and center $c_2$, $(c_2,r_2)$, are externally tangent. Then we have $$ \begin{align} |c_1-c_2|^2&=(r_1+r_2)^2\tag{1a}\\ |c_1|^2-2c_1\cdot c_2+|c_2|^2&=r_1^2+2r_1r_2+r_2^2\tag{1b} \end{align} $$ For a given sphere, $(c,r)$, the radius of the inverted sphere, $\bar{r}$, satisfies $$ \begin{align} \frac{|c|^2}{r^2}-1&=\frac1{r\bar{r}}\tag{2a}\\ |c|^2-r^2&=\frac r{\bar{r}}\tag{2b} \end{align} $$ We don't actually use any of the properties of spherical inversion, so we can simply take $(2)$ as a definition of $\bar{r}$.

Thus, if we subtract $r_1^2+r_2^2$ from both sides of $\mathrm{(1b)}$ and use equation $\mathrm{(2b)}$, we get $$ \begin{align} \frac{r_1}{\bar{r}_1}+\frac{r_2}{\bar{r}_2}-2c_1\cdot c_2&=2r_1r_2\tag{3a}\\ \frac{c_1}{r_1}\cdot\frac{c_2}{r_2}-\frac{1}{2}(\frac{1}{\bar{r}_1r_2}+\frac{1}{r_1\bar{r}_2})&=-1\tag{3b} \end{align} $$ Furthermore, from equation $\mathrm{(2a)}$, we get $$ \frac{|c|^2}{r^2}-\frac{1}{r\overline{r}}=1\tag{4} $$ Therefore, if, for a sphere in $\mathbb{R}^n$, $(c,r)$, we define the row vector in $\mathbb{R}^{n+2}$ $$ v=\left\langle\frac cr,\frac1r,\frac1{\bar{r}}\right\rangle\tag{5} $$ and make a square matrix, $V$, from $n+2$ of these row vectors for $n+2$ mutually tangent spheres, then we get from equation $\mathrm{(3b)}$, for the off-diagonal elements, and equation $(4)$, for the diagonal elements, that $$ V\left[\begin{array}{c c c} I_n & 0_{n\times 1} & 0_{n\times 1} \\ 0_{1\times n} & 0 & -\frac{1}{2} \\ 0_{1\times n} & -\frac{1}{2} & 0 \end{array}\right]V^T = 2I_{n+2}-C_{n+2}\tag{6} $$ where $C_{n+2}$ is an $(n{+}2)\times(n{+}2)$ matrix of all $1$s. Because $C_{n+2}^2=(n+2)C_{n+2}$, it is easily verified that $$ (2I_{n+2}-C_{n+2})^{-1}=\frac{1}{2}I_{n+2}-\frac{1}{2n}C_{n+2}\tag{7} $$ Invert equation $(6)$ and move $V$ to the right side to get $$ \left[\begin{array}{c c c} I_n & 0_{n\times 1} & 0_{n\times 1} \\ 0_{1\times n} & 0 & -2 \\ 0_{1\times n} & -2 & 0 \end{array}\right] = V^T(\frac{1}{2}I_{n+2}-\frac{1}{2n}C_{n+2})V\tag{8} $$ Looking at the $(n+1,n+1)$ element of the matrix equation $(8)$, we get the equation $$ n\sum_{k=1}^{n+2}\frac{1}{r_k^2}=\left(\sum_{k=1}^{n+2}\frac{1}{r_k}\right)^2\tag{9} $$ If one of the spheres encompasses the rest, so that all the other spheres are internally tangent to it, then equation $\mathrm{(1a)}$ becomes $|c_1-c_2|^2=(r_1-r_2)^2$. If we consider the radius of the encompassing sphere to be negative, then this becomes $|c_1-c_2|^2=(r_1+r_2)^2$ as before. Therefore, we will consider the radius of an encompassing sphere to be negative.

Thus, we have shown

The Soddy-Gosset Theorem: Given $n+2$ mutually tangent spheres in $\mathbb{R}^n$, their radii, $\{r_k:1\le k\le n+2\}$ satisfy equation $(9)$ if the radius of an encompassing sphere is considered negative.

Furthermore, if we look at the $(j,n+1)$ elements of the matrix equation $(8)$, for $1\le j\le n$, we get the vector equation $$ n\sum_{k=1}^{n+2}\frac{c_k}{r_k^2}=\sum_{k=1}^{n+2}\frac{c_k}{r_k}\;\sum_{k=1}^{n+2}\frac{1}{r_k}\tag{10} $$ If we divide equation $(10)$ by equation $(9)$, we get $$ \frac{\displaystyle\sum_{k=1}^{n+2}\frac{c_k}{r_k^2}}{\displaystyle\sum_{k=1}^{n+2}\frac{1}{r_k^2}} =\frac{\displaystyle\sum_{k=1}^{n+2}\frac{c_k}{r_k}}{\displaystyle\sum_{k=1}^{n+2}\frac{1}{r_k}}\tag{11} $$ Thus, we have derived the following

Corollary: Given $n+2$ mutually tangent spheres in $\mathbb{R}^n$ with radii $\{r_k:1\le k\le n+2\}$, the mean of the centers weighted by $\frac1{r_k^2}$ is equal to the mean of the centers weighted by $\frac1{r_k}$.

Conclusions from Soddy-Gosset

Given the radii of $n+1$ mutually tangent spheres in $\mathbb{R}^n$, the Soddy-Gosset Theorem allows us to compute the radius of two possible spheres that are tangent to the other $n+1$. That is, we can solve $(9)$ for $\frac1{r_{n+2}}$: $$ n\left(\color{#C00000}{\frac1{r_{n+2}^2}}+\sum_{k=1}^{n+1}\frac1{r_k^2}\right) =\color{#C00000}{\frac1{r_{n+2}^2}}+2\color{#C00000}{\frac1{r_{n+2}}}\sum_{k=1}^{n+1}\frac1{r_k}+\left(\sum_{k=1}^{n+1}\frac1{r_k}\right)^2\tag{12a} $$ $$ (n-1)\color{#C00000}{\frac1{r_{n+2}^2}}-2\color{#C00000}{\frac1{r_{n+2}}}\sum_{k=1}^{n+1}\frac1{r_k}+n\sum_{k=1}^{n+1}\frac1{r_k^2}-\left(\sum_{k=1}^{n+1}\frac1{r_k}\right)^2=0\tag{12b} $$ applying the quadratic formula to $(12)$, we get $$ \frac{n-1}{r_{n+2}}=\sum\limits_{k=1}^{n+1}\frac1{r_k}\pm\sqrt{n}\left[\left(\sum\limits_{k=1}^{n+1}\frac1{r_k}\right)^2-(n-1)\sum\limits_{k=1}^{n+1}\frac1{r_k^2}\right]^{1/2}\tag{13} $$ Note that the discriminant in $(13)$ vanishes precisely when the first $n+1$ spheres satisfy the Soddy-Gosset Theorem on $\mathbb{R}^{n-1}$. This implies that $\{c_k:1\le k\le n+1\}$ lie in an $n-1$ dimensional hyperplane, and the two possibilities for $(c_{n+2},r_{n+2})$ are reflections of each other across this hyperplane.

Conclusions from the Corollary

Given the radii of $n+2$ mutually tangent spheres and the centers of the first $n+1$ of them, the Corollary allows us to determine $c_{n+2}$, except in the case where the coefficients of $c_{n+2}$ cancel in $(11)$. That is, when $$ \frac{\dfrac1{r_{n+2}^2}}{\displaystyle\sum_{k=1}^{n+2}\frac{1}{r_k^2}} =\frac{\dfrac1{r_{n+2}}}{\displaystyle\sum_{k=1}^{n+2}\frac{1}{r_k}}\tag{14} $$ which is equivalent to $$ \begin{align} \frac1{r_{n+2}} &=\frac{\displaystyle\sum_{k=1}^{n+2}\frac1{r_k^2}}{\displaystyle\sum_{k=1}^{n+2}\frac1{r_k}} =\frac{\displaystyle\sum_{k=1}^{n+1}\frac1{r_k^2}}{\displaystyle\sum_{k=1}^{n+1}\frac1{r_k}}\tag{15a,15b}\\ &=\frac1n\sum_{k=1}^{n+2}\frac1{r_k} =\frac1{n-1}\sum_{k=1}^{n+1}\frac1{r_k}\tag{15c,15d} \end{align} $$ Explanation:
$\mathrm{(15a)}$: restatement of $(14)$
$\mathrm{(15b)}$: multiply $\mathrm{(15a)}$ by $\sum\limits_{k=1}^{n+2}\frac1{r_k}$, subtract $\frac1{r_{n+2}^2}$, then divide by $\sum\limits_{k=1}^{n+1}\frac1{r_k}$
$\mathrm{(15c)}$: apply $(9)$ to $\mathrm{(15a)}$
$\mathrm{(15d)}$: multiply $\mathrm{(15c)}$ by $n$, subtract $\frac1{r_{n+2}}$, then divide by $n-1$

Note that $\mathrm{(15b)}$ and $\mathrm{(15d)}$ say that the first $n+1$ spheres satisfy the Soddy-Gosset Theorem in $\mathbb{R}^{n-1}$. Again, this implies that $\{c_k:1\le k\le n+1\}$ lie in an $n-1$ dimensional hyperplane.

Furthermore, $\mathrm{(15d)}$ matches $(13)$ when the discriminant vanishes.

Locating $\boldsymbol{c_{n+2}}$ in the Exceptional Case

By rotation and translation, we can arrange that the $n-1$ dimensional hyperplane containing $\{c_k:1\le k\le n+1\}$ is $x_n=0$. That is, if $1\le k\le n+1$, $$ c_{k,n}=0\tag{16} $$ and $c_{n+2,n}$ is the perpendicular distance of $c_{n+2}$ above or below that hyperplane. For clarity of presentation, let $\hat{p}$ be the projection of $p$ onto the hyperplane $x_n=0$; that is, $\hat{p}_k=p_k$ for $1\le k\le n-1$ and $\hat{p}_n=0$.

Looking at the $(j,n)$ elements of matrix equation $(8)$ for $1\le j\le n-1$, we get the vector equation $$ \begin{align} \frac{\hat{c}_{n+2}}{r_{n+2}} &=\frac1n\sum_{k=1}^{n+2}\frac{\hat{c}_k}{r_k}\tag{17a}\\ &=\frac1{n-1}\sum_{k=1}^{n+1}\frac{c_k}{r_k}\tag{17b} \end{align} $$ which, in light of $\mathrm{(15d)}$, gives the vector equation $$ \hat{c}_{n+2}=\frac{\displaystyle\sum_{k=1}^{n+1}\frac{c_k}{r_k}}{\displaystyle\sum_{k=1}^{n+1}\frac1{r_k}}\tag{18} $$ Looking at the $(n,n)$ element of matrix equation $(8)$ we get $$ \begin{align} 1 &=\frac12\frac{c_{n+2,n}^2}{r_{n+2}^2}-\frac1{2n}\frac{c_{n+2,n}^2}{r_{n+2}^2}\\ &=\frac{n-1}{2n}\frac{c_{n+2,n}^2}{r_{n+2}^2}\tag{19} \end{align} $$ which gives us $$ c_{n+2,n}=\pm r_{n+2}\sqrt{\frac{2n}{n-1}}\tag{20} $$ We can now remove the rotation, and use $(18)$ and $(20)$ to get that $$ c_{n+2}=\frac{\displaystyle\sum_{k=1}^{n+1}\frac{c_k}{r_k}}{\displaystyle\sum_{k=1}^{n+1}\frac1{r_k}}\pm ur_{n+2}\sqrt{\frac{2n}{n-1}}\tag{21} $$ or equivalently, using Soddy-Gosset and the Corollary in $\mathbb{R}^{n-1}$ and $\mathrm{(15b)}$, $$ \frac{c_{n+2}}{r_{n+2}}=\frac{\displaystyle\sum_{k=1}^{n+1}\frac{c_k}{r_k}\frac1{r_k}}{\displaystyle\sum_{k=1}^{n+1}\frac1{r_k}}\pm u\sqrt{\frac{2n}{n-1}}\tag{22} $$ where $u$ is a unit vector perpendicular to the plane containing $\{c_k:1\le k\le n+1\}$.

  • $\begingroup$ I am wanting to reference your proof and I was wondering if I could have a link to the paper you wrote on this? Either that of there or how you would like it to be referenced? Thanks $\endgroup$ – Tessa Danger Bamkin Mar 2 '15 at 11:22
  • $\begingroup$ @TessaDangerBamkin: It would be better to cite this answer, as it is more complete than the paper. Cite this answer as is described in this blog. $\endgroup$ – robjohn Mar 2 '15 at 14:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.